Marketing Capability as a Source of Sustainable Competitive Advantage from the Perspective of Resource-Based Theory in Telecommunication Companies in Indonesia - Saputra, Devid; Fadilah, Emil; Mendrofa, Ilham (LPPM Universitas Jambi, 2026)
This study aims to analyze how leading telecommunications companies in Indonesia, PT Telkom Indonesia Tbk, PT Indosat Ooredoo Hutchison Tbk (IOH), PT XLSMART Telecom Sejahtera Tbk, and PT Dayamitra Telekomunikasi Tbk (Mitratel) transform internal resources and capabilities into market-based assets as a basis for sustainable competitive advantage in the period 2022–2025. Using a qualitative document analysis on official annual reports, the framework combines Resource-Based Theory and VRIO Framework with Resource-Advantage Theory of Competition, market-based assets, brand equity, customer equity, marketing capabilities, and service-dominant logic. Findings show that competitive differentiation is increasingly determined by market-based relational and intellectual assets, rather than solely physical asset ownership. IOH built its advantage through